2005
DOI: 10.1093/aob/mci071
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth and Endosperm Cell Size Under High Night Temperatures in Rice (Oryza sativa L.)

Abstract: Background and Aims High night temperatures are more harmful to grain weight in rice than high day temperatures. Grain growth rate and growth duration were investigated to determine which was the cause of the decrease in final grain weight under high night temperatures. Endosperm cell number and cell sizes were also examined to determine which might cause the decrease in final grain weight.Methods Rice plants were grown outdoors in plastic pots and moved at heading time to three temperaturecontrolled glasshous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
159
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(180 citation statements)
references
References 30 publications
9
159
3
Order By: Relevance
“…Despite these methodological differences compared with previous studies, our findings corroborate recent ones that T min has a large, negative impact on yield (8,30). Although the mechanisms responsible for the negative impact have yet to be conclusively identified (4), our results could be explained by increased respiration losses during the vegetative phase (8) and reduced grain-filling duration and endosperm cell size during the ripening phase (31).…”
Section: Discussionsupporting
confidence: 89%
“…Despite these methodological differences compared with previous studies, our findings corroborate recent ones that T min has a large, negative impact on yield (8,30). Although the mechanisms responsible for the negative impact have yet to be conclusively identified (4), our results could be explained by increased respiration losses during the vegetative phase (8) and reduced grain-filling duration and endosperm cell size during the ripening phase (31).…”
Section: Discussionsupporting
confidence: 89%
“…As compared to maximum temperature, increase in minimum temperature had more pronounced negative impacts on Swarna yield. This more pronounced negative impact of minimum temperature on rice yield could be explained by increased respiration losses during the vegetative phase (Peng et al, 2004) and reduced grain-filling duration and endosperm cell size during the ripening phase (Morita et al, 2005).…”
Section: Sensitivity Analysis On Climatic Adaptationsmentioning
confidence: 99%
“…They apprehended that these high temperature injuries were due to disappearance of enzyme activity relating to starch synthesis of the grains. Furthermore, Morita et al (2005) reported that high night temperature (22/34ºC, day/night) induced higher reduction of fi nal grain weight and growth rate of rice in early-and mid-stage of grain fi lling along with the reduction of cell size compared with high day temperature (34/22ºC, day/night). Moreover, the rice grain grown at 38/21ºC temperature contained more chalky grains (Lisle et al, 2000).…”
mentioning
confidence: 99%